Sharing or gambling? On risk attitudes in social contexts - Martin G. Kocher; Michal Krawczyk; Fabrice Le Lec (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
This paper investigates experimentally whether risk attitudes are stable across social contexts. In particular, it focuses on situations where some resource (for instance, a position, decision power, a bonus) has to be allocated between two parties: the decision maker can either opt for sharing the resource or for using a random device that allocates the entire prize to one of the two parties. By varying the relative situation of the decision maker with respect to the other party, we show that risk attitude is strongly affected by social contexts: participants in the experiment seem to be relatively risk seeking when they possess a relatively weaker position than the other party and risk averse when the opposite is true. Our main average results seem to be driven by the behavior of around a quarter of subjects whose choices appear to be fully determined by social comparisons. Various interpretations of the behavior are provided linking our results to preferences under risk with a social reference point and on status-seeking preferences.
urn:nbn:de:bvb:19-epub-17383-7
Keywords: A13; C65; C72; D63; D03; 330; risk attitudes; risk preferences in social context; social reference point; status-seeking preferences; social preferences under risk